NILAI EKONOMI BUAH-BUAHAN SEBAGAI HASIL HUTAN BUKAN KAYU DI DESA KAMPUNG TENGAH, KECAMATAN MEMPURA, KABUPATEN SIAK - enny insusanty; ambar tri ratnaningsih; aziz akbar mukasyaf (Jurnal Ilmiah Ekonomi Dan Bisnis, 2017)
Abstract: Non-wood forest products (HHBK) such as fruits are a source of income for the community. The purpose of this study was to measure and assess the potential economic value of non-timber forest products from the fruit trees in the village of Kampung Central District of Mempura and calculate the contribution of HHBK fruits of the income of the people in the village of Kampung Central District of Mempura. The method used is survey by taking samples purposively to farmers who take HHBK it the fruit such as durian, manggris, rambutan and other kinds in the village of Middle Village Kecamata Mempura in Siak. Data analysis was conducted by qualitative descriptive. The types of products HHBK main fruit used by the villagers of Kampung Central District of Mempura Siak is durian, mangosteen and rambutan. Potential production of durian, mangosteen, and rambutan respectively 7350 / year, 8100 / year, and 29200 / year. The economic value of HHBK fruit products that provide the greatest contribution to public revenue Kampung Desa Central District of Mempura Siak is durian to the economic value of Rp 257.25 million (90.15%), mangosteen Rp 13,500,000 (4.73%) and rambutan Rp 14.6 million (5.12%). The total economic value of the use of a limited range of products of fruits in the village of Middle Village, District Mempura, Siak Regency was Rp 285.35 million. The revenue contribution of the average value of the product is 33.53% HHBK durian, mangosteen and rambutan while the 2.64% and 2.92%.Keywords:Potential, Economics, Fruits, Non-wood Forest Products